February–May 2018. (23rd August 2018) - Cranmer, Frank
Abstract : On 23 March, the European Council agreed the terms of a Brexit transition period under which the United Kingdom's phased departure will last for 21 months, ending in December 2020. The European Union (Withdrawal) Bill completed its consideration in the House of Lords with Government defeats on several issues, perhaps the most controversial of which were amendments requiring the Government to explore the option of staying in a customs union (by a majority of 123), limiting the ability to use secondary legislation to change existing EU rights after they have been transposed into domestic law (by a majority of 97) and retaining most of the EU Charter of Fundamental Rights on the statute book after Brexit (by a majority of 71).